A successful vitrification technique for goat morulae conservation - Fernandez, Jimena (2022)
The aim of this study was to evaluate the effect of different vitrification and warming processes on the in vitro embryo survival of caprine morulae, considering the day of recovery. A total of 136 morulae of Criolla-Neuquina goats recovered on Days 7 or 8 after sponge removal, were exposed to three different vitrification processes; V1 (n ¼ 48): glycerol (G) þ ethylene glycol (EG); V2 (n ¼ 44): EG þ 0.5 M sucrose and V3 (n ¼ 44): G þ EG þ 0.5 M sucrose. The morulae of each vitrification process were randomly assigned to three warming processes; W1 (n ¼ 45): 0.5 M sucrose at 25°C; W2 (n ¼ 44): 0.5 M sucrose at 39°C; and W3 (n ¼ 47): solution containing half the concentration of the cryoprotectants þ 0.5 M sucrose at 25°C. After, embryos were cultured in 100 mL TCM 199 drops under mineral oil, at 39°C and a 6.5% CO2 atmosphere for 72 h according to the different treatments. There were no viable embryos in V1 and V2 in none of their three respective warmings. Only V3 showed an embryo survival rate to hatched blastocyst stage of 59.1%. When considering embryo survival according to the warming processes, the survival rate was higher in V3W2 (76.9%) and V3W3 (66.7%) groups compared to the V3W1 group (37.5%; P < 0.05). The embryo survival of V3 for Day 8 after sponge removal (81.3%) was higher compared to Day 7 (46.4%; P < 0.05). In conclusion, a successful embryo survival is obtained by using a combination of cryoprotectants (G þ EG) with addition of sucrose in the vitrification process for conservation of caprine morulae in embryo transfer programs. The survival rates in vitro of vitrified-warmed morulae in goats were influenced by their recovery day. Further studies should be conducted to determine if these results are reproducible in vivo embryo transfer on field situations.